Three new species of Dikrella Oman (Hemiptera: Cicadellidae: Typhlocybinae) from Minas Gerais State, Brazil - Coelho, Luci Boa Nova; Nessimian, Jorge Luiz (Zootaxa, 2009)
Dikrella aculeata sp. nov., D. reticulata sp. nov. and D. spinifera sp. nov. are described and figured based on male specimens obtained from light trap collections at Mata do Paraíso, Municipality of Viçosa, State of Minas Gerais, Brazil. The genus Dikrella is recorded from Minas Gerais for the first time.